Indicators for Sustainable Energy Development for Austria (ISED-AT). Residential Buildings and Electricity and Heat Supply - Claudia Kettner; Daniela Kletzan-Slamanig; Angela Köppl (Austrian Institute of Economic Research (WIFO), 2015)
A transformation of prevailing energy systems requires adequate measurement systems. In this paper we propose an energy-service based indicator set and a composite index for monitoring sustainable energy development in the residential sector and electricity and heat supply in Austria. The system of Indicators for Sustainable Energy Development for Austria (ISED-AT) and the composite index focus on energy services instead of energy flows and are hence effective tools for monitoring and guiding the transition, as they allow assessing the whole range of technology options for providing a particular energy service. The analysis of household final energy demand and electricity and heat supply in Austria shows substantial progress in terms of ecological aspects, such as the share of renewable energy sources and CO2 emissions. With respect to energy efficiency, in contrast, only little improvement can be observed. Efficiency of energy service provision is decreasing except for heating and air conditioning. Final energy demand is rising in all areas of household energy demand. The challenge lies in a substantial improvement of energy efficiency that will allow an absolute decoupling of energy service demand from final energy consumption.
Keywords: 330; sustainable energy development; indicator set; composite index; residential buildings; energy supply